Implementation of biological variation-based analytical performance specifications in the laboratory: Stringent evaluation of Improvacutor blood collection tubes. - Hee-Jung Chung; Yoon Kyung Song; Sung Kuk Hong; Sang-Hyun Hwang; Hee Seung Seo; Dong Hee Whang; Myung-Hyun Nam; Do Hoon Lee; Do Hoon Lee (PLoS ONE, 2017)
Recently, because the quality of laboratory analyses has increased along with the need for quality improvement, several external quality control bodies have adapted performance specifications using the Desirable Biological Variation Database, termed "Ricos goals"; these criteria are more stringent than those presented in CLIA 88. In this study, we aimed to validate newly introduced serum separator tubes, Improvacutor, for routine clinical chemistry testing in accordance with Ricos goals and CLIA 88. Blood samples were collected from 100 volunteers into three types of serum vacuum tubes: Greiner Vacuette, Becton Dickinson (BD) Vacutainer, and Improve Improvacutor. The samples were subjected to 16 routine chemistry tests using a TBA-200fr NEO chemistry autoanalyzer. In the comparison analysis, all 16 test results were acceptable according to CLIA 88. However, in the comparison of Improve and BD tubes, creatinine showed 4.31% (+0.08 μmol/L) bias. This slightly exceeded the Desirable Specification for Inaccuracy Ricos limit of ±3.96%, but still satisfied the CLIS88 limit of ±26.52 μmol/L. The remaining 15 analytes performed acceptably according to the Desirable Specifications of Ricos. The correlation coefficient of 12 analytes was greater than 0.95 in Passing-Bablok regression analysis among the three tubes, but was lower for four analytes: calcium, sodium, potassium, and chloride. In the stability assay, only potassium tested in the Greiner tube revealed a larger positive bias (2.18%) than the Ricos Desirable Specification for Inaccuracy based on biologic variation (1.8%). The BD tube also showed a positive bias of 1.74%, whereas the new Improve tube showed the smallest positive bias of 1.17% in potassium level after 72 h storage. Thus, the results of this study demonstrate that recently introduced analytical performance specifications based on components of biological variation (Rico's goal) could be extended to criterion for performance evaluation and applied.